RICH KID SMART KID : GIVING YOUR CHILD A FINANCIAL HEAD START - KIYOSAKI, ROBERT T.; LECHTER, SHARON (WARNER BOOKS USA, 2000)
This book was designed to fill in the gaps : to help you give your child the same inspiring and practical financial knowledge that authors father gave him.
Keywords: CHILD PSYCHOLOGY